Role of communication in preparation of patient for gynecological operative procedure - Bączek, Grażyna; Sobolewska, Marzena; Dmoch-Gajzlerska, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Interpersonal communication is exchange of information between sender and recipient We observe different behavior communication in hospital departments. Communication with patient has significant influence on process of diagnosing, treatment and cherishing - in this case of patient prepared for gynecological operative procedure. Purpose of work is presentation of role and meanings of suitable communications in process of preparation of patient for gynecological operative procedure with taking into consideration role of midwife. In article it discuss theoretical bases in turn before operative, characteristic of operative procedure, meaning of state emotive patient before procedure and intercommunication with patient prepared for procedure.